TEMPERATURE MEASUREMENT COMPUTATIONS IN SURFACE SURFACE WITH DIFFERENT METHODS - Masduki Zakarijah (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2003)
This research goal to heat transfer rate prediction on every node insurface line and the difference of temperature measurement between direct measurement and numerical analysis based on Matlab with finite difference technique. Object of this research is aluminium plate to take shape a plaid square with size 5 x 22 em to divided in 75 node. The result of this research is heat transfer rate on every node in surface line between direct measurement and numerical analysis based on Matlab not difference of significance.